Men’s Language and Masculine Identity Construction in Sexist Jokes - Emi Nursanti (Journal of English Language Teaching and Linguistics, 2022)
The power imbalance between men and women in society is reflected in their language use and it may be reinforced in sexist jokes. This is a sociolinguistic study on men’s language in sexist jokes on the Internet. This study is aimed at investigating men’s linguistic features and the masculine identities represented by those features. This is a descriptive qualitative study with complementary quantitative analysis. The theories of Tannen’s men language (1990) and Kiesling’s masculine identities (2007) were used as references to analyze the data. The results show that men’s identity of competing for solidarity embodied in discourses of insults, teasing, and joking is the most dominant identity represented in sexist jokes. This is in line with the main intention of sexist humor to laugh at women’s inferiority. Meanwhile, men’s dominance realized in report talk becomes the second most prevalent identity. The identities of politeness oaf, indicated by direct command, and freedom, shown by swearing and taboo words, are not influential as both do not contribute to the making of humorous expressions. These imply that context and communication purposes motivate speakers to use gender-related features. Reflecting that most of the masculine identities and the language features in sexist jokes represent men’s superiority, this kind of humor can be a way to maintain gender asymmetry in society. Besides, although humor leads to laughter and is considered healthy, sexist humor is dangerous as the expressions subordinate women. Therefore, being critical when reading the jokes and trying to avoid such jokes in communication is suggested.